Circular RNA circTMEM45A Acts as the Sponge of MicroRNA-665 to Promote Hepatocellular Carcinoma Progression - Zhang, Tingting (Mol Ther Nucleic Acids, 2020)
Mounting evidences indicate that circular RNAs (circRNAs) play vital roles in the development and progression of various cancers. However, the detailed functions and underlying mechanisms of circRNAs in hepatocellular carcinoma (HCC) remain largely unknown. The expression profile of circRNAs was screened by circRNA microarrays. Quantitative real-time PCR was used to determine the level-10 circRNAs selected from the top five upregulated (hsa_circ_0001955, hsa_circ_0001535, hsa_circ_0061395, hsa_circ_0000502, and hsa_circ_0066659) and top five downregulated circRNAs (hsa_circ_0046366, hsa_circ_0003418, hsa_circ_0026134, hsa_circ_0005692, and hsa_circ_0014130). The effects of circTMEM45A in HCC cells were studied both in vitro (in a Cell Counting Kit-8 assay, apoptosis analysis, and cell cycle assays) and in vivo (by means of tumor xenografts in nude mice). Luciferase reporter, RNA immunoprecipitation (RIP), and rescued assays were used to confirm the interactions between circTMEM45A, miR-665, and insulin growth factor 2 (IGF2). We found that the level of circTMEM45A was significantly upregulated in HCC and was positively correlated with clinicopathological features and poor prognosis of patients with HCC. Functionally, circTMEM45A promoted cell mobility in vitro, as well as in vivo tumorigenesis. Mechanistically, circTMEM45A acted as a miR-65 sponge to relieve the repressive effect of miR-665 on its target IGF2. Moreover, circTMEM45A was upregulated in serum exosomes from HCC patients. circTMEM45A promotes HCC progression through the miR-665/IGF2 axis and may serve as a novel diagnostic marker and target for treatment of HCC patients.